Rescuing popular knowledge and using unconventional food plants as a possibility of nutritional security (Research, Society and Development, 2022)
Unconventional food plants (UFP) are those with limited distribution, restricted to certain locations, with great participation in the nutrition and culture of traditional populations. UFP are among the sources of food that develop in natural environments without the need for inputs and deforestation of new areas, but although available at low cost, they are still unknown and underutilized by a significant portion of the population. The present study aimed to analyze the dynamics of eating habits and survey UFP in agrarian reform settlements in the municipality of Maragogi, state of Alagoas. To collect information on the use of UFP, questionnaires were applied and data were tabulated in electronic spreadsheet and transformed into tables. In settlements evaluated, between twelve and fourteen different UFP were identified in the social context of these communities. There are several UFP options that could be marketed by the population, thus contributing to increase family income.